2004
DOI: 10.1554/04-189
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Effects of Female Mate Choice in Wild Threespine Sticklebacks

Abstract: Abstract. Sexual selection by mate choice represents a very important selective pressure in many animal species and might have evolutionary impacts beyond exaggeration of secondary sexual traits. Describing the shape and strength of the relationships linking mating success and nonsexual traits in natural conditions represents a challenging step in our understanding of adaptive evolution. We studied the effect of behavioral (nest site choice), immunological (trematode level of infection), genetic diversity (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 92 publications
0
21
0
Order By: Relevance
“…2008). Moreover, previous work within the SW deme of the St. Lawrence system revealed an effect of parasite load on reproductive success (Blais et al. 2004).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…2008). Moreover, previous work within the SW deme of the St. Lawrence system revealed an effect of parasite load on reproductive success (Blais et al. 2004).…”
Section: Discussionmentioning
confidence: 91%
“…2005). While this approach may be beneficial in terms of separating the role of MHC from other traits, it cannot be forgotten that actual mate choice is multimodal (Blais et al. 2004) and that absence of complete information can potentially bias outcomes (Nilsson & Nilsson 2000; McLennan 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Canonical analysis of the matrix of nonlinear selection gradients allows an interpretation of stabilizing and disruptive selection to be made on trait combinations that describe the greatest amount of nonlinear variation on fitness surfaces (Phillips and Arnold 1989; Simms 1990; Simms and Rausher 1993; Blows and Brooks 2003). Although canonical analysis has been advocated for > 15 years (Phillips and Arnold 1989; Simms 1990), its potential utility in empirical studies and meta‐analyses has only recently become more widely appreciated (Björklund and Senar 2001; Blows and Brooks 2003; Blais et al 2004; Brooks et al 2005; Bentsen et al 2006; Holleley et al 2006; Blows 2007a,b; Garant et al 2007; Hunt et al 2007; Kruuk and Garant 2007).…”
Section: Applications Of Quadratic Selection Coefficientsmentioning
confidence: 99%
“…This study showed that male colour and reproductive success are unaffected by parasites for males in Lynne Lake, which is consistent with some populations of G. aculeatus but not others (FitzGerald et al ., ; Bakker & Mundwiler, ; Kraak et al ., ; Blais et al ., ; Macnab et al ., , ). For Lynne Lake, one possible explanation for this relationship is that males are generally in good condition and can tolerate infection more effectively.…”
mentioning
confidence: 99%